A choice of point of view and picture plane in the apparatus of central projection - Nitsyn, A. (Theory and practice of design, 2015)
In the article formulation and proof of assertions about the choice of point of view in the main point of picture and choice of distance from the center of projection to the picture plane for the increase of accuracy of transmission of depth of space on the plane of picture is resulted.